PsycEXTRA Dataset 2011
DOI: 10.1037/e520602012-241
|View full text |Cite
|
Sign up to set email alerts
|

Testing Theories of Post-Error Slowing

Abstract: People tend to slow down after they make an error. This phenomenon, generally referred to as post-error slowing, has been hypothesized to reflect perceptual distraction, time wasted on irrelevant processes, a priori bias against the response made in error, increased variability in a priori bias, or an increase in response caution. Although the response caution interpretation has dominated the empirical literature, little research has attempted to test this interpretation in the context of a formal process mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 50 publications
(83 reference statements)
0
20
0
Order By: Relevance
“…Second, neither study found an effect of depression on decision threshold. Consequently, the results do not simply reflect a speed-accuracy trade-off in depressed participants, because such a trade-off should yield a threshold difference (Dutilh et al, 2012). …”
Section: Discussionmentioning
confidence: 94%
“…Second, neither study found an effect of depression on decision threshold. Consequently, the results do not simply reflect a speed-accuracy trade-off in depressed participants, because such a trade-off should yield a threshold difference (Dutilh et al, 2012). …”
Section: Discussionmentioning
confidence: 94%
“…To further investigate and provide converging evidence for this strategic shift across the lifespan, we calculated the degree to which individuals slowed down responses following an incorrect response. This phenomenon, referred to as post-error slowing, is thought to reflect error monitoring (Dutilh, et al, 2012). To better isolate post-error slowing, across the group we regressed out the mean reaction time for correct trials immediately preceding an error trial from the mean reaction times for correct trials immediately following an error trial.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, there is a general tendency for individuals to slow their reaction time (RT) on trials following an error, consistent with behavioral adjustment (Rabbitt, 1966). It has been proposed that this post-error slowing (PES) reflects an increase in response caution following an error (Botvinick et al, 2001; Dutilh et al, 2012). …”
Section: Error Monitoring and Adjustmentmentioning
confidence: 99%